PENGARUH PENGGUNAAN MEDIA RODA PUTAR UNTUK MENINGKATKAN KETERAMPILAN MEMBACA BAHASA ARAB SISWA KELAS VIII MTS ISLAMIYAH KEMBANGBAHU LAMONGAN - Sa’ada, Nisa’us; Umroh, Ida Latifatul (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2025)
This research was motivated by the low Arabic reading skills of students at Mts Islamiyah Kembangbahu Lamongan. Low reading ability is influenced by the conventional learning process without using media to support learning activities. Therefore, researchers want to improve students' reading skills by using rotary wheel learning media. This media is used to train students to read and understand reading content, it is also used to increase student learning motivation. The purpose of this study is (1) to determine the use of rotary wheel media in improving Arabic reading skills. (2) To determine the improvement of Arabic reading skills of grade VIII students of MTS Islamiyah Kembangbahu Lamongan using rotary wheel media. In this thesis research, researchers used a quantitative approach using quasi-experimental methods of non-equivalent qontrol group type design. Data collection techniques used in this study are observation sheets, tests and documentation. The data obtained were then analyzed using descriptive statistical data analysis and inferential data analysis. The results showed that before being treated in the experimental group, there were 7 students who were complete (41%) and 8 students who were incomplete (59%) with an average score of 72.00 which was relatively low. Meanwhile, in the control group, there were 6 students who completed (41%) and 9 students who were incomplete (59%) with an average score of 71.00 which was relatively low. As for after being given the application of the use of rotary wheel media to the experimental group, there were 13 students who were complete (97%) and 2 students who were incomplete (3%) with an average score of 83.67 which was classified as high. While the results of the control group data as a whole there were 7 students who were complete (41%) and 8 students who were incomplete (59%) with an average score of 74.67. So it can be known that the average value of the pretest and posttest has increased, but it is superior to the experimental group compared to the control group. So it can be concluded that the use of rotary wheel media can significantly improve the Arabic reading skills of grade VIII students of Mts Islamiyah developing lamongan.